KINERJA EFISIENSI FUNGSI INTERMEDIASI BANK PERSERO DI INDONESIA DENGAN MENGGUNAKAN DATA ENVELOPMENT ANALYSIS (DEA) - Andi Wijayanto; Sutarno Sutarno (Jurnal Keuangan dan Perbankan, 2010)
The purposes of this study were to measure the ef f iciency level of state bank inIndonesia, to ident if y which bank had the best ef f iciency level, and to f ind ef f iciency determinantsof state bank in Indonesia. Analyt ical technique used was the DEA (Data EnvelopmentAnalysis). Input and output variables used intermediary funct ion of Starvarek model.Four banks were chosen as samples by using purposive sampling. The result of the studyshowed that state bank in Indonesia had a good relat ively ef f icient level. BRI, BTN, and BankMandiri had a relat ive ef f iciency level reaching 100%, while BNI was the only bank that wasrelat ively inef f icient with relat ive ef f iciency score 88.5%. Number of human resources, thetotal variable credit and short term securit ies became the dominant determinant of the ef f iciencyof state banks in Indonesia. Inef f icient companies should have increased ef f iciency byperforming input or output maximizat ion. Although the BRI, BTN, and Bank Mandiri hadproven relatively high eff iciency, the efficiency was not a peak performance they could achieve,meaning that the current level of ef f iciency could st ill be improved higher by input and/oroutput maximizat ion; potent ial improvements that could be achieved by BNI were reducingthe f ixed assets and sof tware, the amount of labor, the total deposit (input ) and increasingthe total credit .